Implementation of the Gamification-Based Blooket Platform in Learning to Listen to Fantasy Fairy Tales - Novita U. Hundolo; Salam; Eka sartika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study was conducted in response to the current state of fantasy fairy tale listening instruction, which remains dominated by lecture-based methods and thus fails to effectively enhance student motivation and engagement in the learning process. The study aims to describe the implementation of the gamification-based Blooket platform in fantasy fairy tale listening instruction for seventh-grade students at SMP Negeri 1 Telaga during the 2025/2026 academic year. The study employed a qualitative descriptive approach supported by quantitative descriptive data. The research subjects consisted of one Indonesian language teacher and 20 seventh-grade students. Data were collected through observation, interviews, tests, questionnaires, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, and was reinforced through triangulation of sources and methods. The research results indicate that the implementation of the Blooket platform was carried out through the stages of planning, implementation, and evaluation of learning, which were based on the Merdeka Curriculum teaching modules. The learning process took place through introductory, core, and concluding activities by utilizing gamification features such as competitions, challenges, and immediate feedback. Test results indicate that most students achieved scores above the Minimum Passing Criteria (KKM), while survey results show a very positive response to the use of Blooket, particularly regarding learning motivation, engagement, interaction, and ease of use. The success of the implementation was supported by student readiness, teacher competence, and the availability of learning facilities and infrastructure. The challenges identified included differences in student abilities, limited learning time, and technical obstacles such as internet connectivity and supporting devices. The research findings indicate that the use of the Blooket platform positively contributes to student engagement and supports the comprehension of fantasy story texts.